ANALISIS PERSEPSI DAN HUBUNGAN PRESTASI BELAJAR MATEMATIKA DENGAN PRESTASI BAHASA PEMROGRAMAN - Herlina Herlina; Teady Matius Surya Mulyana (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2020)
Mathematics is the basis before learning coding-based courses. This type of research is quantitative descriptive. Sample of 110 informatics engineering students. The results of the study showed a significant association of learning outcomes in mathematics with the achievement of learning programming languages. The magnification coefficient of 0.663 has a moderate and positive meaning. The contribution of mathematics in explaining programming languages ​​is 43.97% and the remaining 56.03% is accepted by other variables. Students' perceptions of mathematics and programming languages ​​consist of four levels of understanding, namely the five senses, analysis, interpretation and evaluation. Every level of dimension. On the sensory dimension of 31.9% mathematics has a close relationship with programming languages. In the dimensions of analysis and interpretation, the value of the percentage of perceptions that are almost the same namely 21.24% and 21.14% associate mathematical concepts with the concepts of programming languages. In the evaluation dimension of 20.6%, it shows that in programming languages, students need information other than mathematics, namely the purpose of the programming language that is being designed. Full Article